A comprehensive review of platelet-rich plasma for the treatment of dermatologic disorders. (31st December 2023) - Pixley, Jessica N.; Cook, Madison K.; Singh, Rohan; Larrondo, Jorge; McMichael, Amy J.
Abstract: Platelet-rich plasma (PRP) offers anti-inflammatory and regenerative properties through angiogenesis, cell differentiation, and proliferation. Although studied in many dermatologic conditions, its efficacy is not well-understood. Our objective is to review the use and effectiveness of PRP for dermatologic conditions. A literature search was performed through PubMed and yielded 54 articles published between January 2000 and November 2021; articles written in English were reviewed. Intradermal injections were associated with increased hair density in androgenic alopecia. Successful treatment of inflammatory nail diseases with PRP has been reported. Improvement in psoriasis was described, but only two studies were available. PRP was associated with higher patient self-assessment scores of photoaging and fine lines. Treatment with PRP in melasma has been associated with improved subjective satisfaction, but not with objective measures of disease improvement. PRP can serve as a safe and potentially effective adjunct for hair loss, vitiligo, nonhealing wounds, photoaging, and acne scars. An important barrier to interpreting PRP research is lack of standardization of PRP preparation protocols, inconsistent clinical endpoints, and frequent combination treatments. However, PRP is relatively noninvasive, has a well-established safety profile, and patient satisfaction is often high as patients perceive great benefit from treatment with PRP.